Synthesis, Antidiabetic Evaluation and Molecular Docking Studies of Thiazolidine-2,4-Dione Analogues - Pardeshi, Dolly R; Kulkarni, Vithal M; Pathare, Sandeep S (Indian Journal of Pharmaceutical Education and Research, 2023)
Introduction: Diabetes Mellitus is a disorder of metabolism described by high glucose levels. The disorder kills a larger number of individuals consistently than of malignant growth and AIDS combined. Presently available drugs have several drawbacks forcing to withdraw from treatment. The potent side effect i.e., hepatotoxicity and cardiovascular toxicity limits the use of thiazolidine-2,4-dione derivative as safe drugs. Our aim is towards the development of synthetic compounds as potential antidiabetic agents, particularly preparation and screening of new analogues of thiazolidine-2,4-dione (TZD) which are well established as oral insulin sensitizing agents that improve insulin resistance and are agonists of Peroxisome Proliferator Activated Receptor–γ (PPAR-γ). Materials and Methods: Proper substitution at C-5 position of thiazolidine-2,4-dione could produce better and potential antidiabetics with improved pharmacological properties, including toxicity. Our aim of this research work is towards this. Results: A series of C-5 substituted thiazolidine-2,4-dione analogues were synthesized. Structures of these new analogues were confirmed by IR, 1H-NMR and MASS spectroscopy. Among the synthesized compounds, three compounds: 5-(2-pyridinylbenzylidene) thiazolidine-2,4-dione, 5-(3,4-dimethoxybenzylidene) thiazolidine-2,4-dione and 5-(2,3,4-trifluorobenzylidene) thiazolidine-2,4-dione showed significant antidiabetic activity in streptozotocin induced diabetic mice comparable with Pioglitazone drug. The molecular docking studies of these compounds performed using protein target showed amino acid interactions with Leu270, Gln283 and Arg288 similar with that of Rosiglitazone and Pioglitazone. The compounds did not show any toxic effect in mice even at 2000 mg/kg of dose. Therefore, synthesis of modified and better thiazolidine-2,4-dione containing drugs other than the currently available drugs is of importance in antidiabetic drug research.
Keywords: Thiazolidine-2,4-dione; Molecular docking; Antidiabetic evaluation; Swiss albino mice